1994
DOI: 10.1159/000263932
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Tissue Collection from Spontaneous Abortions: A Report from a Single Centre

Abstract: Due to immunological immaturity, the fetus is the ideal recipient as well as donor of haemopoietic stem cells (HSCs); thus intrauterine therapy may prove to be effective in all major haemopoietic disorders when early prenatal diagnosis is available. In man, ‘fetus-to-fetus’ transplantation has demonstrated the possibility of grafting donor HSCs and reconstituting immunodeficient fetuses. The limitations of fetal tissue use for transplantation derive from the origin of tissues from elective abortions. Early and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…More over, our results strongly support the concept of the age-related and tissue-specific ontogen ic differences in the phenotypic composition and functional capacity of FBM and ABM [ 12,[33][34][35][36], These results strongly support the utilization of spontaneously aborted fetal tis sue, provided that the tissue is well selected in terms of viability and freedom of any contam ination (viral, bacterial, fungal, and genetic). The high number of CD34+ cells, when com pared to other sources of stem cells, clearly suggested that this is the stem cell population of choice for hemopoietic stem cell reconstitu tion and gene therapy as an ideal target cell population [37], In fact, data obtained by oth er investigators confirmed the efficacy of stem cells from miscarriages [38,39], Thus, it sup ports our initial hypothesis that this untapped source of viable cells could be utilized. The 380 Feial Diagn Tlicr 1996:11:373-382 M ichcjda/Bcllanti/M azum der/Vcrm a/ Wu tissue should be examined for any contamina tion and stored properly in a tissue bank for utilization in life-saving transplantations [13,14].…”
Section: Lr Assaysmentioning
confidence: 96%
“…More over, our results strongly support the concept of the age-related and tissue-specific ontogen ic differences in the phenotypic composition and functional capacity of FBM and ABM [ 12,[33][34][35][36], These results strongly support the utilization of spontaneously aborted fetal tis sue, provided that the tissue is well selected in terms of viability and freedom of any contam ination (viral, bacterial, fungal, and genetic). The high number of CD34+ cells, when com pared to other sources of stem cells, clearly suggested that this is the stem cell population of choice for hemopoietic stem cell reconstitu tion and gene therapy as an ideal target cell population [37], In fact, data obtained by oth er investigators confirmed the efficacy of stem cells from miscarriages [38,39], Thus, it sup ports our initial hypothesis that this untapped source of viable cells could be utilized. The 380 Feial Diagn Tlicr 1996:11:373-382 M ichcjda/Bcllanti/M azum der/Vcrm a/ Wu tissue should be examined for any contamina tion and stored properly in a tissue bank for utilization in life-saving transplantations [13,14].…”
Section: Lr Assaysmentioning
confidence: 96%